Conceptual cost estimation framework for modular projects: a case study on petrochemical plant construction - Choi, Younguk; Park, Chan Young; Lee, Changjun; Yun, Sungmin; Han, Seung Heon (Journal of Civil Engineering and Management, 2022)
Modularization, which allows for pre-assembly away from a construction site, has been known to be more cost-effective than stick-built; however, contractors have difficulty ascertaining the benefits and adopting it. Calculating the benefits and costs of adopting modularization precedes decision making. However, modular cost estimation is challenging since relevant information in the early stages of a project and historical data about industrial modularization both have limited availability. To solve this problem, this study developed a conceptual cost estimation framework for industrial modular projects by converting stick-built project information. The framework is composed of eight steps based on two approaches. This study conducted a case study to demonstrate the applicability of the framework, which compared the project cost of modularization scenarios 1 and 2 with that of the stick-built version of the ongoing project. In addition, the estimated modular cost was compared with the engineers’ estimation to verify the accuracy of the framework. The contributions of this study are in identifying and quantifying the factors influencing the differences in cost between the modularization and stick-built versions, and developing the conceptual cost estimation framework for an industrial modular project. This framework is expected to support deciding on adopting modularization, budgeting, and project viability.